Zika virus: An emerging challenge for obstetrics and gynecology - Jhe-Jhih Lin; Ting-Yu Chin; Chih-Ping Chen; Hong-Lin Chan; Tzong-Yuan Wu (Elsevier, 2017)
Microcephaly is a rare birth defect, however, the re-emerging mosquito and sexual transmitted flavivirus, Zika virus (ZIKV), had changed the situation and caused an urgent challenge for the obstetrics and gynecology. This review will brief summarize the epidemiology and virology of ZIKV. And compared the animal models that had developed for the ZIKV infections. These animal models will be benefit for the development of vaccines and anti-ZIKV drugs. Furthermore, the genes that are involved in the causation of microcephaly were also summarized. Finally, the Wnt signal is critical for the brain development as well as innate immune response. Based on previous literatures, we proposed that ZIKV-induced microcephaly might result from the influence of Wnt/β-catenin signaling pathway through the regulation of miRNA-34.